Repurposing statins for the treatment of larval cestodiases: in silico evaluation of statin-HMG-CoA reductase interactions and assessment of statin effects on a cestode model - Monteiro Guedes, Marina (2024)
Cestodiases, like echinococcoses and cysticercoses, represent a global health problem. Currently available anthelmintics, as benzimidazoles and praziquantel, have limited effectiveness against these cestodiases, creating a demand for the identification of new and more effective drugs. Here, the potential of statins (simvastatin and fluvastatin), for repositioning as novel anthelmintic is explored. Statins are inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, a main enzyme in the mevalonate pathway, which is vital for the synthesis of non-steroidal isoprenoids and the maintenance of normal cell functioning. A survey for HMG-CoA reductase encoding genes showed that they are present in a single copy in the genomes of parasitic helminths and their mammal hosts. Sequence alignments and phylogenetic analyses showed 20?95% overall identities among ortholog HMG-CoA reductases, with special conservation of their catalytic domains. The HMG-CoA reductase 3D-structure was predicted for orthologs from 3 cestodes of medical importance (Echinococcus multilocularis, Echinococcus granulosus sensu lato, and Taenia solium), and from a model cestode species (Mesocestoides corti). Molecular docking between cestode HMG-CoA reductase orthologs with simvastatin demonstrated that the Arg, Ser, Lys, and Glu residues in conserved positions of the active site interact with this drug, similarly to the interactions predicted for the human reference ortholog enzyme. Furthermore, in vitro assays demonstrated that simvastatin produced a significant reduction of M. corti viability, being able to reduce 100% of parasite viability at 150 μm. Fluvastatin was also assessed showing a lower, although significant anthelmintic effect. The predicted overall structures and interactions together with in vitro assays suggest that cestodes HMG-CoA reductases are inhibited by simvastatin, being a potential therapeutic target for the repurposing of simvastatin as anthelmintic drug. Furthermore, these results pave the way for the in vivo evaluation of the potential effects of simvastatin on cestode larvae.